2021
DOI: 10.1177/03635465211047858
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Baseline Characteristics and Outcome Among Responders, Late Responders, and Never-Responders After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Loss to follow-up in registry studies might affect generalizability and interpretation of results. Purpose: To evaluate the effect of nonresponder bias in our anterior cruciate ligament (ACL) registry. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 2042 patients with ACL reconstruction in the Hospital for Special Surgery ACL Registry between 2009 and 2013 were included in the study. Patients who completed the patient-reported outcome measures at 2 or 5 years were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(28 reference statements)
2
7
1
Order By: Relevance
“…In addition to young age and smoking, previous studies of non-respondents also reported a predominance of the male gender, living alone, and higher preoperative disability at baseline (2,(4)(5)(6)(17)(18)(19). However, these ndings were not reproduced in our study.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In addition to young age and smoking, previous studies of non-respondents also reported a predominance of the male gender, living alone, and higher preoperative disability at baseline (2,(4)(5)(6)(17)(18)(19). However, these ndings were not reproduced in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have demonstrated that non-respondents are younger than respondents (2,4,(17)(18)(19). Completing and posting questionnaires consumes time, and younger patients may be more busy due to work and family obligations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have conducted an in-depth analysis of nonresponders and have not found significant differences in outcome or revision rates between responders and nonresponders. 26 Furthermore, cartilage lesions were assessed only by size, not depth, and our study did not have enough power to analyze the effect of the location in the knee joint of the cartilage lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that non-respondents are younger than respondents [ 2 , 4 , 16 – 19 ]. Completing and posting questionnaires consumes time, and younger patients may be busier due to work and family obligations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to young age and smoking, previous studies of non-respondents also reported a predominance of the male gender, living alone, higher anxiety levels, and worse PROM scores [ 2 , 4 – 6 , 16 – 19 ]. Two observational spine studies found that non-respondents had higher ODI scores, lower quality of life (EuroQol 5D), and lower function (Short form health survey—SF-36) preoperatively compared to those who responded [ 2 , 19 ].…”
Section: Discussionmentioning
confidence: 99%